2019
DOI: 10.1016/j.ijnss.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a training program based on maker education for baccalaureate nursing students: A quasi-experimental study

Abstract: Objectives Maker education is a dominant force in education reform and is viewed as a revolutionary way to learn. As innovative pedagogy is continuously explored in the field of nursing, the emerging role of maker education must be examined. This research aims to build a nursing bachelor education program based on maker education and to evaluate the effectiveness of this program. Methods Forty volunteer junior students majoring in nursing from a college were the subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“… 58 59 A quasi-experimental study concluded that a training programme based on maker education improved students’ creativity, learning interest and cooperative learning ability. 60 The learning environment directly affected students’ learning methods and academic achievements, and satisfaction with the learning environment could in turn encourage students to adopt a more positive approach to learning. 61 Therefore, to improve the SDL ability of nursing students, it is indispensable to create an adaptive learning environment.…”
Section: Discussionmentioning
confidence: 99%
“… 58 59 A quasi-experimental study concluded that a training programme based on maker education improved students’ creativity, learning interest and cooperative learning ability. 60 The learning environment directly affected students’ learning methods and academic achievements, and satisfaction with the learning environment could in turn encourage students to adopt a more positive approach to learning. 61 Therefore, to improve the SDL ability of nursing students, it is indispensable to create an adaptive learning environment.…”
Section: Discussionmentioning
confidence: 99%
“…There are some research results showing that maker education has the advantages of openness, compatibility, sharing, and practicality. It also helps to cultivate students' creative ability (Yang et al, 2019). Maker education is a new type of teaching strategy that focuses on learning by doing and provides many exercises to stimulate students' creativity and innovation ability.…”
Section: Maker Educationmentioning
confidence: 99%
“…There are some research results showing that maker education has the advantages of openness, compatibility, sharing, and practicality. It also helps to cultivate students’ creative ability ( Yang et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The maker mindset is seen to be related to important competencies such as innovative ideas and actions (Kang, 2017 ), critical thinking, creativity, problem solving and collaboration (Kang and Yoon, 2017 ), etc. ME has the advantages of openness, compatibility, sharing, and practicality, which helps to cultivate students' creative ability (Yang et al, 2019 ). In addition, ME is closely related to the learning principle of constructivism, which also emphasizes “learning by doing” in educational theory (Kim, 2018 ; Yoon, 2018 ; Kim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%